Reforming Skills Development, Transforming the Nation: South African Vocational Education and Training Reforms, 1994–2005 - McGrath, Simon (2009)
Keywords: openalex:import

Lifelong learning in South Africa: critical reflections on developments since 1994 - McGrath, Simon (International journal of continuing engineering education and life-long learning, 2009)
In the run up to its first democratic elections in 1994, South Africa became one of the first countries to make a serious commitment to developing a qualifications framework-based lifelong learning system. This was intended both to prepare the country for its insertion into 'the global knowledge economy' after years of isolation and to provide a way of dealing with the legacy of Apartheid. Through an exploration of the most recent data on education and training in South Africa, this paper points to the limited achievement of this vision. It argues that the intrinsic and symbolic logics of a lifelong learning system have been overwhelmed by institutional logic and political economy, resulting in a system that exists in name only that has not reached the most marginalized. The paper concludes with a suggestion that the gap between the rhetoric and reality of qualifications framework-based lifelong learning is not simply a result of South Africa's particular context but a matter of importance to the growing number of countries, particularly in Asia, that are embarking upon similar approaches.
Keywords: openalex:import

Vocational education and training for sustainability in South Africa: The role of public and private provision - McGrath, Simon; Akoojee, Salim (International journal of educational development, 2009)
Written in the twilight of the Mbeki Presidency, this paper considers the role that skills development has in the sustainability of the South African political–economic project. It explores some of the disarticulations of public policy and argues that these both undermine public sector delivery and open up opportunities for private provision to be, under certain circumstances, more responsive to the challenges of national development. We argue that there is a possibility that the state could work more smartly with both sets of providers. Crucially, however, this would necessitate working more smartly within itself. This was a major plank of the Mbeki strategy but it has failed conspicuously with regard to the Education–Labour relationship. Whether a new President can achieve a radical reworking of this relationship may be an important indicator of the viability of any new development project. The article concludes with reflections on the renewed international interest in skills development as a way of responding to the real and imagined pressures and opportunities of globalisation. Given the limited success of South Africa in pursuing skills development, we ask whether other African governments are any more likely to achieve a genuine combination of political, social and economic sustainability. The sustainability of national development projects in Africa is likely to continue to be problematic, and skills development will only ever be able to play a limited role in addressing this challenge. Nonetheless, governments can do more to support the sustainability of these skills development systems and need to pay attention to both public and private provision in so doing.
Keywords: openalex:import